Current and potential alternative food uses of the Argentine anchoita (Engraulis anchoita) in Argentina, Uruguay and Brazil - Madureira, Lauro Antonio Saint Pastous (2009)
A comparative assessment between the use of the Argentine anchoita (Engraulis anchoita) for reduction fisheries and human food and/or value-added products is the focus of this case study. General biological aspects, spatial and seasonal distribution and available biomass estimates of the target species are examined. Currently applied and promising potential methods of processing anchoita in Argentina, Brazil and Uruguay are described and compared in terms of economic and nutritional impact. Engraulis anchoita is a small pelagic fish that occurs in the South West Atlantic Ocean (SWAO) with Brazil, Uruguay and Argentina sharing the so-called anchoita "Bonaerense" stock. Annual abundance estimates vary between 600 000 tonnes and 4.5 million tonnes, with significant regional and yearly variations in biomass estimates along the shelves of the three countries. Fishing takes place predominantly between July and November. Catches in 2006 were reported to be around 30 000 tonnes in Argentina and 17 000 tonnes in Uruguay. It is estimated that up to 135 000 tonnes of anchoita could be sustainably exploited along the southern Brazilian coast. However, despite its abundance, this species is not fished there. The three countries exhibit different approaches to the utilization of E. anchoita. Argentina is the pioneer in the exploitation and manufacture of anchoita and the main manufacturer of different kinds of products for human consumption directed to both the domestic and export markets. More than 80 percent of this production is salted fish and the remainder is prepared as value-added food. In 2005, Argentine exported anchoitabased products at a value of US$26 million. At present, Uruguay processes its anchoita catch exclusively as fishmeal for export, although the preparation of products for human consumption is planned for the near future. Due to its unexploited fishery resources as well as considerable demand, Brazil has great potential for manufacturing new products that could contribute to both the domestic and export markets. Trial products have been developed that could address food security and poverty alleviation in the region and elsewhere. Alternative potential uses for new products from anchoita were assessed on the basis of prototypes developed in Brazil. It is concluded that novel products such as dehydrated risotto, soup and sausage have considerable strategic marketing value. An assessment of the costs and benefits of the production of fishmeal and new products for human consumption in Brazil revealed that the transformation of anchoita for human consumption results in significantly higher direct positive impacts on poverty and food security. Governmental social programmes supporting school meals and hospital diets are a promising entry point for the introduction of novel products to nutritionally challenged parts of society. The search for common solutions for improved utilization of anchoita should evolve from a strong technical-scientific interaction and mutual collaboration among the governments of the three countries.